DEVELOPMENT OF VIRIAL EQUATION OF STATE FOR GAS PHASE PROPANE AND BUTANE - Firchan Jeehad, Emiral
LPG is one kind fuel which is used for household purposes. It contains propane, normal butane, isobutane and other constituent compounds. The constituent compound of LPG can be used as an alternative refrigerants since they have zero ODP value and 3 values of GWP. For various application requirements, the thermodynamic properties of LPG need to be known. The way to find out thermodynamic properties of a substance is by conducting experiments. Experimental data cannot provide thermodynamic properties at all state so that the thermodynamic properties of substance is need to be predicted using equation of state. Virial equation of state has a basic theory that can be considered to predict thermodynamic properties. Virial equation of state in this study was obtained by an empirical approach. The thermodynamic properties of PVT, heat capacities, and speed of sound data are optimized by least squares regression method combined with genetic algorithm. Optimized equation is helmholtz equation of state obtained from the integration of pressure functions based on the potential theory of Lennard-Jones and square well toward density. Virial equation of state with Lennard-Jones theory had relatively good reliability compared to square well theory. Virial equation of state based on Lennard-Jones potential cannot compete with the helmholtz equation because of the limitations of the term and fewer nonlinear variables compared to helmholtz equation. Extrapolation behavior of PVT properties, isobaric heat capacity and speed of sound based on square well theory have a large deviation at high pressure compared to helmholtz equations, meanwhile virial equation based on Lennard-Jones potential theory have the same trend tendency as the helmholtz equation.